SWOT Analysis to Encourage Entrepreneurial Innovation in Building a Sustainable Economy - Sukendri, Nengah (Guna Sewaka, 2025)
This study aims to analyze entrepreneurial innovation in building a sustainable economy in the Hampers business in Mataram City. The method in this study uses a qualitative approach. Data collection techniques were carried out through interviews, direct documentation and continued with the distribution of questionnaires to hampers business actors Bloomy.bloo, Gift_Thetic, Buket_Lombok / Mitha Florist, The Floral Waves, Galleryartistik, and Kamihandycraft. Data analysis techniques are carried out by reducing data, presenting data, concluding and verifying data with SWOT analysis. Sustainable economy can be interpreted as an economic activity that focuses on common welfare that can contribute positively and benefit producers and consumers, and not only pay attention to economic growth. Business actors must be able to pay attention to sustainable development economic activities by considering social, economic and environmental aspects. SWOT analysis is an effective strategic tool in encouraging entrepreneurial innovation for a sustainable economy. This approach enables the creation of business models that are adaptive to market changes, support long-term economic growth, and contribute to sustainable development. The entrepreneurial innovation strategy results in a SWOT matrix strategy, namely by identifying strengths, weaknesses, opportunities, and threats, businesses can develop innovative strategies that are not only economically profitable, but also pay attention to social and environmental aspects.